(untitled) (Cambridge, 1990)
The intensive study of particular localities and communities characterizes much recent work in social history. Volume One draws on this approach to present a series of chapters on the social history of various regions of the British Isles.
Keywords: Social institutions,Associations, institutions, etc.,Tổ chức xã hội,Hiệp hội, tổ chức...; History,History,Lịch sử,Lịch sử; Great Britain,Great Britain,Anh quốc,Anh quốc